Research and Exploration for PON Resource Automatic Discovery - Yanbin Shi; Gengshu Su; Zhiming Yang (Dianxin kexue)
The problem which the difference between resource data and existing network data,resources data and network management data hinder the telecom operator to develop FTTH users and broadband services were discussed.Combined with PON,intelligent ODN and the mobile internet technology,a resource-automatic discovery engine architecture system was built and the automatic matching check of resource data with existing network data consistency was achieved,the efficiency and quality of resource management were enhanced.